Retroviral vectors: post entry events and genomic alterations - Nowrouzi, Ali; Glimm, Hanno; Kalle, Christof von; Schmidt, Manfred (Viruses, 2011)
The curative potential of retroviral vectors for somatic gene therapy has been demonstrated impressively in several clinical trials leading to sustained long-term correction of the underlying genetic defect. Preclinical studies and clinical monitoring of gene modified hematopoietic stem and progenitor cells in patients have shown that biologically relevant vector induced side effects, ranging from in vitro immortalization to clonal dominance and oncogenesis in vivo, accompany therapeutic efficiency of integrating retroviral gene transfer systems. Most importantly, it has been demonstrated that the genotoxic potential is not identical among all retroviral vector systems designed for clinical application. Large scale viral integration site determination has uncovered significant differences in the target site selection of retrovirus subfamilies influencing the propensity for inducing genetic alterations in the host genome. In this review we will summarize recent insights gained on the mechanisms of insertional mutagenesis based on intrinsic target site selection of different retrovirus families. We will also discuss examples of side effects occurring in ongoing human gene therapy trials and future prospectives in the field.